Initial rheological description of high performance concretes - Castro,Alessandra Lorenzetti de (2006)
Concrete is defined as a composite material and, in rheological terms, it can be understood as a concentrated suspension of solid particles (aggregates) in a viscous liquid (cement paste). On a macroscopic scale, concrete flows as a liquid. It is known that the rheological behavior of the concrete is close to that of a Bingham fluid and two rheological parameters regarding its description are needed: yield stress and plastic viscosity. The aim of this paper is to present the initial rheological description of high performance concretes using the modified slump test. According to the results, an increase of yield stress was observed over time, while a slight variation in plastic viscosity was noticed. The incorporation of silica fume showed changes in the rheological properties of fresh concrete. The behavior of these materials also varied with the mixing procedure employed in their production. The addition of superplasticizer meant that there was a large reduction in the mixture's yield stress, while plastic viscosity remained practically constant.